STUDI ANALISIS PERBANDINGAN METODE STARTING DIRECT ON LINE (DOL) DAN VARIABEL SPEED DRIVE (VSD) PADA MOTOR FAN UNTUK COOLING TOWER DI PT. RAPP (RIAU ANDALAN PULP PAPER) - Ivan Putra Naibaho, Martogi; Wijaya, I Ketut; Mataram, I Made (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
The large starting current in the starting process has the potential to damage the induction motor. In minimizing the risk of damage, proper starting methods are needed. The Direct On Line (DOL) method is a starting method commonly used in induction motors because of its economical installation and high work efficiency. The starting method which also has good work efficiency is the Variable Speed Drive (VSD). There needs to be a comparative analysis between the two methods to find out how the performance of the two methods is. Research results, the ongoing performance of the two starting methods on the fan motor for cooling towers shows that the performance of the VSD method is superior to that of the DOL method. Starting performance on an induction motor can be seen from the efficiency and economic value of the DOL and VSD methods. This performance is of course taking into account the current, rotation speed and the resulting output power.